Policy entrepreneurship in the reform of pediatric dentistry - Burton L. Edelstein; William R. Maas (BMC, 2017)
Abstract In a recently published IJHPR article, Cohen and Horev ask whether an individual who holds rightful governmental power is able to effectively "challenge the equilibrium" in ways that might "clash with the goals" of an influential group". This question is raised within the context of a shift in governmental policy that imposed the potential for cost management by HMOs acting as financial intermediaries for pediatric dental care in an effort to provide Israeli children better access to affordable dental care. The influential group referred to consists of Israel's private dentists and the individual seeking to challenge the equilibrium was an Israeli Minister of Health whom the authors consider to be a policy entrepreneur. The Israeli health care system is similar to that of the United States in that private benefit plans and self-pay financing dominate in dental care. This is in contrast to the substantial role of government in the financing and regulation of medical care in both countries (with Israel having universal coverage financed by government and the US having government financing the care of the elderly and the poor as well as providing subsidies through the tax system for the care of most other Americans). Efforts to expand governmental involvement in dental care in both countries have either been opposed by organized dentistry or have suffered from ineffective advocacy for increased public investment in dental care. In the U.S., philanthropic foundations have acted as or have supported health policy entrepreneurs. The recent movement to introduce the dental therapist, a type of allied dental professional trained to provide a narrow set of commonly-needed procedures, to the U.S. is discussed as an example of a successful challenge to the equilibrium by groups supported by these foundations. This is a somewhat different, and complementary, model of policy entrepreneurship from the individual policy entrepreneur highlighted in the Cohen-Horev paper. The political traction gained to change the equilibrium favored by organized dentistry - in both Israel and the U.S. - may reflect aspirations for care that is more accessible, patient-centered, accountable and equitable. Evolving aspirations may lead to policy changes to systematize the disparate, disaggregated dental care delivery system in both counties. A change in payment incentives to provide more value is being explored for medical care, and its expansion to dental care can be anticipated to be among the policies considered in the future.